Adherence to monitoring of patients treated with amiodarone: a nationwide study - Frenkel, Amit; Smadar Shneyour, Ruth; Shiloh, Adi; Morad, Mohammed; Shimoni-Rachmilev, Orly; Dreiher, Jacob (Frontiers in Medicine, 2024)
The aim of this study was to assess the adherence to monitoring guidelines regarding amiodarone treatment.Methods: This is a retrospective cohort study of data recorded in Clalit Health Services, the largest healthcare organization in Israel. Included were individuals aged >18 years; who were prescribed amiodarone and had a documented purchase d amiodarone of this drugfor any indication, for a minimum of 200 consecutive days; and who had less than a 100-day gap between two consecutive purchases during 2013-2021. Adherence was assessed to testing for thyroid, liver function, and electrolytes, as determined by the performance of a test every six months.The study included 24,094 individuals (mean age: 75 years, 53% male). The median follow-up was 2.3 years (total 73,727 person-years). The proportions of patients who performed baseline tests were: 43.4% for thyroid function, 58.3% for electrolytes, 48.6% for liver function, 20.6% for chest X-rays, and 14.9% for electrocardiograms. Adherence rates to semiannual monitoring of thyroid function, liver function, and electrolyte tests were: 70.4%, 79.4%, and 88.3%, respectively. In a multivariable analysis, the factors associated with higher adherence were male sex; older age; the presence of thyroid abnormalities, renal failure, and hypertension; and more frequent visits to the primary care physician.In our country, adherence is low to monitoring risk factors for adverse effects of amiodarone therapy, especially prior to treatment initiation. Patient and primary care physicians should be educated about the importance of monitoring, particularly prior to initiation of amiodarone treatment.